Relationship between seafood consumption and bisphenol A exposure: the Second Korean National Environmental Health Survey (KoNEHS 2012–2014) - Kim, Yeji (Ann Occup Environ Med, 2020)
BACKGROUND: This study aimed to identify the relationship between exposure to bisphenol A (BPA) and seafood consumption using a nationally representative data of the general Korean population. METHODS: This study was conducted on 5,402 adults aged 19 years and older (2,488 men, 2,914 women) based on the second Korean National Environmental Health Survey (2012–2014). We stratified the data according to gender and analyzed urinary BPA concentrations in terms of sociodemographic characteristics, health behavior, dietary factor, and seafood consumption. In the high and low BPA exposure groups, the odds ratios (ORs) were calculated using logistic regression analysis according to the top 75th percentile concentration. RESULTS: In men, large fish and tuna and other seafood categories had significantly higher ORs before and after adjustment in the group who consumed seafood more than once a week than in the group who rarely consumed seafood, with an adjusted value of 1.97 (95% confidence interval [CI]: 1.12–3.48) and 1.74 (95% CI: 1.10–2.75), respectively. In the shellfish category, the unadjusted OR was 1.61 (95% CI: 1.00–2.59), which was significantly higher in the group who consumed seafood more than once a week than in the group who rarely consumed seafood. However, the OR after adjusting for the variables was not statistically significant. In women, the frequency of seafood consumption and the concentration of urinary BPA were not significantly associated. CONCLUSIONS: BPA concentration was higher in men who frequently consumed large fish and tuna, shellfish and other seafood in this study.